Technical and economic viability of manual harvesting coffee yield maps - Faria, Rafael de Oliveira; Silva, Fábio Moreira da; Ferraz, Gabriel Araújo e Silva; Herrera, Miguel Angel Diaz; Barbosa, Brenon Diennevan Souza; Alonso, Diego José Carvalho; Soares, Daniel Veiga (Coffee Science - ISSN 1984-3909, 2020)
Precision coffee growing is a concept that implies the use of precision agriculture techniques in coffee plantations. For the coffee growing, the precision electronic resources coupled to the harvesters are very scarce. Thereby, the harvest of coffee plantations that compose the grid sampling for generation of thematic maps can be performed manually. The aim of the present study was to generate a linear regression model to estimate the time required to harvest, estimate the labor costs to harvest manually the georeferenced sample points for generation of coffee yield maps. The study was performed in a coffee area of 56 hectares using two sampling points per hectare, totaling 112 points, being evaluated four coffee plants for each point. The manual harvest of the points was performed by four rural workers with experience in the coffee harvest. Afterwards, the collected volume was measured by a graduated container and the times were obtained by the digital stopwatch. Based on the data obtained in the field, a linear correlation model was established between the harvest time of each sampling point and the yield of the point, whose R² value was 78.27, cost was R$ 8.92 per point. These results are relevant for estimating the amount of labor force required to generate manually harvest yield maps according to the producer’s coffee yield estimate, contributing to the closure of the precision coffee growing cycle. Key words: Precision agriculture; crop mapping; field efficiency; costs.